Perceptions of ad hoc entrustment, the need for supervision, and coping strategies in clinical residents: a qualitative study - Lerch, Seraina Petra; Huwendiek, Sören; Nendaz, Mathieu; Klöppel, Stefan; Pinilla, Severin (Academic medicine, 2025)
Purpose: Negotiating the balance between clinical residents’ roles as health care practitioners and learners is a struggle in postgraduate medical education. Although ad hoc entrustment has been studied in this context, little is known about residents’ perceptions of ad hoc over- and underentrustment, the need for supervision, and their coping strategies. Therefore, this study explored residents’ perspectives concerning these topics. - Method: The authors conducted semistructured, in-depth interviews with 12 purposively sampled residents in the graduate medical educational phase of residency who were involved in geriatric psychiatry rotations from different training sites and settings in Switzerland. The interviews were conducted between January and March 2022. Researchers used a thematic analysis to explore and interpret the data within a constructivist research paradigm. - Results: Four overarching themes were identified: ad hoc and default entrustment in the workplace, perceptions of supervision, applied coping strategies to over- and underentrustment, and suggestions for improvement. Residents described entrustment decisions in the workplace as a default, often covert process and as an explicit, ad hoc delegation of clinical tasks. Perceived optimal supervision entailed sufficient time, frequency, and availability of the supervision, supervisors referring to scientific evidence in their reasoning, trustworthiness, and a psychologically safe learning environment. Residents described suboptimal supervision as lacking appropriate feedback timing, having little or nonexistent time in general, using an ambivalent communication style, and clinical decision-making by the supervisor that is not explicit. Residents applied instrumental, appraisal-focused, and emotion-focused coping strategies. Their suggestions for improvement included instructional design of the workplace-based curriculum, supervision, teaching content, and contextual factors. - Conclusions: Within postgraduate training, addressing the organizational and contextual factors of entrustment and resident supervision is essential. Default entrustment decisions need to be explored and explicitly addressed to prevent overentrustment, meet residents’ need for supervision, and effectively coach residents to maintain their well-being.